Melting curve analysis in canine lymphoma by calculating maximum fluorescence decrease. (9th March 2016) - Schöpper, I.; Ohmura, S.; Rütgen, B.; Tsujimoto, H.; Weber, K.; Hirschberger, J.
Abstract: PARR is widely used in the diagnostics of canine lymphoma. In human and veterinary medicine, melting curve analysis (MCA) has successfully been introduced to facilitate the process. Since visual interpretation of melting curves can be rather subjective, the purpose of this study was to develop an objective interpretation of melting curves by calculating the maximum fluorescence decrease (dFmax ) within a defined rise of temperature. Lymph node aspirates and blood of 34 dogs with lymphoma and 28 control dogs were tested. 27/34 lymphoma cases were correctly detected to be monoclonal (sensitivity 79%). 2/28 control dogs showed a monoclonal rearrangement (specificity 93%). B‐ and T‐cell neoplasia were still detectable using DNA amount as low as 10 ng. In serial dilutions of tumor DNA with DNA of normal tonsils, the detection limit was 25% for B‐cell lymphomas and 100% for T‐cell lymphoma, suggesting that PCR conditions could still be optimized.